Effectiveness of heat stress interventions among outdoor workers: a protocol paper - Sankar, Sajeeth Kumar; P, Vijayalakshmi; S, Krishnan; Shanmugam, Rekha; Kamalakkanan, Latha Perumal; Venugopal, Vidhya (Frontiers in Public Health, 2024)
Introduction Heavy work in scorching temperatures can cause dehydration and heat stress, which can lead to a number of heat-related diseases. Heavy work in intense heat without rest or hydration is the main cause. The “Water, Rest, Shade” (WRS) intervention program for outdoor workers in hot weather reduces heat stress. Methods This study follows a quasi-experimental design involving 250 outdoor workers from both agriculture and brick kilns. To assess the environmental heat exposure levels, Quest Temp 3 M WBGT Monitor will be used. Tympanic temperature, Heart rate (HR), Sweat rate (SwR), and Urine specific gravity (USG) to assess the physiological responses to heat exposure using standard protocols. Blood samples will be collected to measure serum creatinine and calculate Glomerular filtration rate (GFR), and urine samples to measure pH, leucocytes, proteinuria, and hematuria. Then administer a validated and modified HOTHAPS questionnaire to capture the perception data. After the baseline assessments, Categorize the workers into two groups based on the selection criteria and the participants’ willingness. Then provide a week-long WRS intervention to the intervention group (IG). The non-intervention group will collect the same data without any intervention to assess the efficacy of the intervention by comparing both groups and measuring outcome indicators. Expected outcome The study will generate much-needed information to raise awareness of the importance of heat stress prevention for outdoor workers. Conclusion This study will demonstrate the effectiveness of an intervention, provide much-needed strategies for reducing heat stress, assess both health impacts and implementation quality, and design comprehensive workplace and labor laws aim to minimise risks to millions of unorganised outdoor workers health.